Deceased-Donor Acute Kidney Injury and BK Polyomavirus in Kidney Transplant Recipients. Issue 5 (8th May 2021) - Hall, Isaac E.; Reese, Peter Philip; Mansour, Sherry G.; Mohan, Sumit; Jia, Yaqi; Thiessen-Philbrook, Heather R.; Brennan, Daniel C.; Doshi, Mona D.; Muthukumar, Thangamani; Akalin, Enver; Harhay, Meera Nair; Schröppel, Bernd; et al.
Visual Abstract: Abstract : Background and objectives: BK polyomavirus (BKV) infection commonly complicates kidney transplantation, contributing to morbidity and allograft failure. The virus is often donor-derived and influenced by ischemia-reperfusion processes and disruption of structural allograft integrity. We hypothesized that deceased-donor AKI associates with BKV infection in recipients. Design, setting, participants, & measurements: We studied 1025 kidney recipients from 801 deceased donors transplanted between 2010 and 2013, at 13 academic centers. We fitted Cox proportional-hazards models for BKV DNAemia (detectable in recipient blood by clinical PCR testing) within 1 year post-transplantation, adjusting for donor AKI and other donor- and recipient-related factors. We validated findings from this prospective cohort with analyses for graft failure attributed to BKV within the Organ Procurement and Transplantation Network (OPTN) database. Results: The multicenter cohort mean kidney donor profile index was 49±27%, and 26% of donors had AKI. Mean recipient age was 54±13 years, and 25% developed BKV DNAemia. Donor AKI was associated with lower risk for BKV DNAemia (adjusted hazard ratio, 0.53; 95% confidence interval, 0.36 to 0.79). In the OPTN database, 22, 537 (25%) patients received donor AKI kidneys, and 272 (0.3%) developed graft failure from BKV. The adjusted hazard ratio for the outcome with donor AKI was 0.7 (95% confidence interval, 0.52 to 0.95). Conclusions: In a well-characterized, multicenter cohort, contrary to our hypothesis, deceased-donor AKI independently associated with lower risk for BKV DNAemia. Within the OPTN database, donor AKI was also associated with lower risk for graft failure attributed to BKV. Podcast: This article contains a podcast at https://www.asn-online.org/media/podcast/CJASN/2021_03_10_CJN18101120_final.mp3